Arsenic, chromium, and copper leaching from CCA-treated wood and their potential impacts on landfill leachate in a tropical country - Karnchanawong S. (2017)
This study looks into the potential risks of arsenic, chromium, and copper leaching from disposed hardwoods treated with chromated copper arsenate (CCA) in a tropical climate. The Toxicity Characteristic Leaching Procedure (TCLP) and the Waste Extraction Test (WET) were employed to examine new CCA-treated Burseraceae and Keruing woods, weathered CCA-treated teak wood, and ash from new CCA-treated Burseraceae wood. In addition, a total of six lysimeters, measuring 2 m high and 203 mm in diameter were prepared to compare the leachate generated from the wood monofills, construction and demolition (CD) debris landfills and municipal solid waste (MSW) landfills, containing CCA-treated Burseraceae wood. The TCLP and WET results showed that the CCA-treated Burseraceae wood leached higher metal concentrations (i.e. 9.19-17.70 mg/L, 1.14-5.89 mg/L and 4.83-23.89 mg/L for arsenic, chromium, and copper, respectively) than the CCA-treated Keruing wood (i.e. 1.74-11.34 mg/L, 0.26-3.57 mg/L and 0.82-13.64 mg/L for arsenic, chromium and copper, respectively). Ash from the CCA-treated Burseraceae wood leached significantly higher metal concentrations (i.e. 108.5-116.9 mg/L, 1522-3862 mg/L and 84.03-114.4 mg/L for arsenic, chromium and copper, respectively), making this type of ash of high concern. The lysimeter study results showed that the MSW lysimeter exhibited higher reducing conditions, more biological activities and more dissolved ions in their leachates than the wood monofill and CD debris lysimeters. All leachates generated from the lysimeters containing the CCA-treated Burseraceae wood contained significantly higher concentrations of arsenic in comparison to those of the untreated wood: in the range of 0.53-15.7 mg/L. It can be concluded that the disposal of CCA-treated Burseraceae wood in an unlined CD landfill or a MSW landfill has the potential to contaminate groundwater.